A Modern Anarchism (Part 1): Anarchist Analysis - Daniel Baryon (libcom.org, 2023)
We stand now at a turning point, wherein many roads sprawl out in front of us. With unprecedented access to information, the atlas seems to lie within our hands. But, at this crossroads, the popularizers of these many paths shout over one another to persuade new travelers, only to find that most travelers now choose tourism rather than migration; exploration rather than arrival. It is hard to blame them. Having seen many return from a path leading to a dead-end, or worse, having lost those they know to a terrible bramble from which they will never escape, these weary travelers are paralyzed by choice. Confused and discouraged, many simply return home where a tormentor awaits, but wherein there is no longer the stress of uncertainty. I would like to tell you of a new path: its extent not yet fully explored, but peering through the forestation beyond, a great light emanates forth. Before we proceed, I would like to pose a question: why has this society accumulated so much power, yet somehow fails to meet the most basic needs of humanity? Why has this hierarchical structure changed hands between so many rulers, yet the peace they have promised never lasts? Their hands bloody, their adherents marching behind, a new society of domination always follows in time. Why? Those intent on creating their own societies of domination will offer all manner of empty excuses. But the true answers lie within an ideology which has been suppressed by the power hoarders: anarchism. This work is not meant to be a brief introduction to the topic. There are plenty of those already in existence. Instead, I want to offer a modern synthesis of anarchist ideas. So, whereas many other books and essays endeavor to give a broad, non-committal overview, here I want to ground you in a particular location within the body of anarchist thought. In doing this, we will not wander down every trail, but we will stop to look at the scenery from time to time. And, for this reason, one might see this work as motivated by the impulse described by Voline in his work On Synthesis: "The anarchist conception must be synthetic: it must seek to become the great living syn-thesis of the different elements of life, established by scientific analysis and rendered fruitful by the synthesis of our ideas, our aspirations and the bits of truth that we have succeeded in discovering; it must do it if it wishes to be that precursor of truth, that true and undistorted factor, not bankrupting of human liberation and progress, which the dozens of sullen, narrow and fossilized 'isms' obviously cannot become." Such a process is, of course, a lofty goal for any one person to carry out. To do this, I will go beyond the standard list of European thinkers that one is typically introduced to when they begin an inspection of this subject. These names will certainly feature in our narrative, as they were very important figures in the development of anarchism as a revolutionary movement. But the ideas of the anarchists are not only important to some specific geographic region. Now, more than ever before, anarchism has achieved a state of critical insight, especially as it has been informed by the work of Black, queer, indigenous, feminist, decolonial, and other anarchist thinkers. All those people who strive to be free of oppression will find their common struggle within its basis. After all, many of these realizations root to the earliest stages of humanity and will likely be at play in any possible human society. Many other anarchist works have failed to take into account these new developments of anarchist theory, to understand where the original struggles have fallen short, and then cooperate alongside this new coalition of thinkers in bringing anarchist principles to their highest culmination. So let us begin...
Keywords: P00; K00; 330; anarchism; capital as power; capitalism; cooperation; creorder; hierarchy; mega machine; power; state